The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1016/0014-5793(93)80162-n
|View full text |Cite
|
Sign up to set email alerts
|

Release of the FAD domain from cellobiose oxidase by proteases from cellulolytic cultures of Phanerochaete chrysosporium

Abstract: Evidence has previously suggested that cellobiose:qumone oxtdoreductase (CBQ) in cellulolytic cultures of Phanerochaete chrysosporium might be produced from cellobiose oxrdase (CBO) by proteolytic cleavage. This study demonstrates that the ratio of CBO activity to (CBO + CBQ) activity declines wtth decreasing culture pH, while protease activity Increases. Furthermore, we demonstrate that endogenous P chrysosporrum proteases can only cleave CBO when the enzyme IS bound to cellulose. This is the first demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…These two domains are linked by a protease-sensitive region (17,35,39,52). Limited proteolytic cleavage of CDH leads to an inactive heme peptide and an active FAD domain, which has been termed cellobiose:quinone 1-oxidoreductase (CBQ; EC 1.5.1.1) (24,54). CBQ carries the catalytic site and reduces cellobiose efficiently.…”
mentioning
confidence: 99%
“…These two domains are linked by a protease-sensitive region (17,35,39,52). Limited proteolytic cleavage of CDH leads to an inactive heme peptide and an active FAD domain, which has been termed cellobiose:quinone 1-oxidoreductase (CBQ; EC 1.5.1.1) (24,54). CBQ carries the catalytic site and reduces cellobiose efficiently.…”
mentioning
confidence: 99%
“…It was formerly known as cellobiose oxidase (CBO, EC 1.1.3.25), but Fe(III)-containing compounds and quinones were found to have much higher affinity for this enzyme than does molecular oxygen (6, 7) so CBO was recently renamed CDH (8). Recent investigations have also demonstrated that another cellobiose-oxidizing flavoprotein, cellobiose:quinone oxidoreductase (CBQ, EC 1.1.5.1) (9,10), is the flavincontaining domain of CDH produced by proteolytic activity (11)(12)(13). In addition to their catalytic function, both CDH and CBQ can bind to cellulose as well as many cellulases (11,14).…”
mentioning
confidence: 99%
“…Sorbitol dehydrogenase and other dehydrogenase detected in present study may be associated with the oxidative degradation of cellulose as proposed [36] in P. chrysosporium. The production of proteases during lignocellulose degradation has been widely reported and their expression has been correlated with the activation of cellulase activity in Sporotrichum pulverulentum [47] and CDH functional domain cleavage in P. chrysosporium [48].…”
Section: Accepted Manuscriptmentioning
confidence: 99%